Study on the Mechanism of Gas Ignition by Friction Effect of Hard Quartz Sandstone Instability. (24th December 2020) - Fuqiang, Li; Guangpeng, Qin; Yonggang, Liu; Qichen, Wang; Ying, Wang; Fengjun, Hou
Abstract : When the upper part of a high gas coal seam has hard and thick sandstone roof, the gas explosion accident in goaf is even caused by roof collapse. Taking the mining of 1007 working face of 10 coal seam under Xia KuoTan Coal Mine as the engineering background, using the method of indoor experiment and theoretical analysis, the possibility of rock friction effect igniting gas is studied. Under the engineering geological conditions, the results show that the heat produced by the friction process of hard sandstone can ignite gas. According to the 3DEC numerical simulation, the instability characteristics of the overburden hard rock are studied. The results show that the size of the slab instability area is not changed when the length of the working face increases. When the thickness of the roof is increased, the area of sliding instability is increased and the degree of sliding instability is more intense. At the boundary of the tunnel, the overlying strata are subjected to the largest shear stress, and it tends to form a friction surface with greater slip instability.